Self-Powered Implantable Skin-Like Glucometer for Real-Time Detection of Blood Glucose Level In Vivo - Zhang, Wanglinhan; Zhang, Linlin; Gao, Huiling; Yang, Wenyan; Wang, Shuai; Xing, Lili; Xue, Xinyu (Nano-Micro Letters, 2018)
Implantable bioelectronics for analyzing physiological biomarkers has recently been recognized as a promising technique in medical treatment or diagnostics. In this study, we developed a self-powered implantable skin-like glucometer for real-time detection of blood glucose level in vivo. Based on the piezo-enzymatic-reaction coupling effect of GOx@ZnO nanowire, the device under an applied deformation can actively output piezoelectric signal containing the glucose-detecting information. No external electricity power source or battery is needed for this device, and the outputting piezoelectric voltage acts as both the biosensing signal and electricity power. A practical application of the skin-like glucometer implanted in mouse body for detecting blood glucose level has been simply demonstrated. These results provide a new technique path for diabetes prophylaxis and treatment. Highlights: 1 Self-powered implantable skin-like glucometer for real-time detection of blood glucose level in vivo was fabricated. 2 The distinct interdigitated electrode ensures piezo-potential of individual nanowires in the same direction. Piezo-biosensing process does not require an external power supply. And the piezoelectric-enzyme-reaction coupling effect is proposed. 3 The device can run well in live mouse and detect in real time the glucose level.